Using exercise to facilitate arousal reappraisal and reduce stress reactivity: A randomized controlled trial. (March 2020) - Jacquart, Jolene; Papini, Santiago; Freeman, Zane; Bartholomew, John B.; Smits, Jasper A.J.
Abstract: Background: Maladaptive stress reactivity is a vulnerability factor for the recurrence of mood and anxiety episodes. Since appraisals of situational demand and available resources to cope with a stressor drive stress reactivity, they are meaningful targets for intervention. In the present study, we test whether exercise (EX) can facilitate learning arousal reappraisal (AR) techniques among individuals vulnerable to depressive episodes and thereby improve reactivity to stressful events. Methods: Participants (N = 167) with mild-to-moderate symptoms of depression were randomly assigned to inactive control (CTRL), EX (three 5-min bouts at varying intensity), AR instruction, or their combination (EX+AR) prior to undergoing a stressor. Stress appraisal (pre- and post-stressor) and perceived stress (pre-, post-, 5-, 10-, and 15-min post-stressor) were assessed. Results: The EX+AR condition reported a more adaptive appraisal of the stressor and exhibited a greater decline in perceived stress immediately and 15-min post the stressor compared to EX and CTRL conditions. The AR condition also reported a more adaptive appraisal of the stressor and exhibited a greater decline in perceived stress but only 15-min after the stressor and only in comparison to the CTRL condition. There were no significant differences between the EX+AR and AR conditions nor between the EX and CTRL conditions. Conclusions: Results provide no clear evidence for a synergistic effect for EX+AR and highlights that AR instruction aids adaptive reappraisal of stress. Studies with longitudinal designs are needed. These observations add to the body of literature exploring mechanisms for improving stress reactivity and the role exercise may play. Highlights: Arousal reappraisal can improve individuals ability to manage stressful events. Exercise alone does not impact individuals ability to manage stressful events. No clear synergistic effect when arousal reappraisal is practiced during exercise. Combining arousal reappraisal with exercise yielded slightly larger effects. Learning arousal reappraisal with a guided exercise experience may be beneficial.